An Integrated Design and Operation Optimal Method for CCHP System. (February 2019) - Zhu, Changbin; Xu, Baoping; Nie, Ya Zhou
Abstract: As a CCHP (combined cooling, heating and power) system becomes more and more complicated, the optimization of capacity configuration and operation strategy turns into a critical issue. In this paper, we put forward a two-layer programming approach which can solve the optimal design and dispatch problem simultaneously. On the first layer, stochastic selection algorithm (SSA) and non-dominated sorting genetic algorithm-II (NSGA-II) are both used to solve the design problem including the optimization of equipment type and capacity, with the goal of minimizing the total lifecycle cost and the pollutant emissions. On the second layer, mixed-integer linear programming (MILP) algorithm is applied to explore a dynamic optimal scheduling scheme, and achieve the lowest operating costs, based on hourly analysis of load characteristics through a whole year. The first layer optimization is based on the optimal results of the second layer. A modelling analysis case of a hospital CCHP system in Chongqing, China is carried out. The economic and environmental goals of Pareto optimality are achieved by applying the two-layer optimization method. The results comparison between SSA and NSGA-II indicates that the former algorithm is much easier and faster, and proofs that the proposed method is reliable.